Effect of Self-Assertiveness Strategy on the Psychological Wellbeing of Widows in Ibadan Metropolis, Oyo State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Widowhood is a significant life event that profoundly impacts the psychological wellbeing of women, particularly in African societies like Nigeria, where cultural expectations and traditional practices often exacerbate the challenges faced by widows. The loss of a spouse typically places widows in emotionally, socially, and economically vulnerable positions, leading to increased risks of depression, anxiety, and other psychological issues. This research examined the effect of self-assertiveness strategy on the psychological wellbeing of widows in Ibadan Metropolis, Oyo State, Nigeria. The survey, which utilised a mixed method approach, adopted a quasi-experimental design with a pretest-posttest approach to assess the effects of self-assertiveness strategy on 38 widows aged between 21-50 years which were used for the study. Participants for the study were divided into an intervention and control groups. Different self-assertiveness exercises were utilised as intervention while the control group received no placebo. The quantitative data were analysed using ANCOVA, tested at <0.05 level of significant and qualitative insights were gathered through focus group discussions. The results from the study indicated that self-assertiveness strategy significantly improved the psychological wellbeing of widows in the intervention group, with an effect size of 57.6% (F(1,36)=48.970, p<0.05, ?2=0.576). The empirical evidence supports the efficacy of self-assertiveness strategies in various psychological and social domains, including self-acceptance, positive relation with others, autonomy, environmental mastery, purpose in life and personal growth. Self-assertiveness training has proven to be beneficial in helping widows express their needs and boundaries in a respectful and effective manner, leading to greater psychological well-being and social functioning. It is recommended to develop culturally and contextually relevant self-assertiveness exercises that acknowledge the unique challenges faced by widows in different settings, and address their specific psychological needs.